Strategic Awareness and its Impact on Organizational Readiness for Change: An Analytical Research into the Automotive and Equipment Manufacturing State Company - AbdHussein Kataa *, Iftikhar; Kadhim Saaed, Hadeel (Journal of Economics and Administrative Sciences, 2024)
The search aims to detect the impact of strategic awareness with its dimensions (awareness of customer service, sales/promotion, product/service, competitive environment, as well as administrative/coordination awareness) as an independent variable on organizational readiness for change with its dimensions (appropriateness, management support, change efficacy, and personal benefits) as a dependent variable. The following questions summarize the main problem of the study: "What is the effect extent of strategic awareness on organizational readiness? and What is the application level of the concept of strategic awareness in the industrial sectors of Iraq?", to reach an actual model that fits the Iraqi environment for employing strategic awareness as an effort for achieving organizational readiness for change. For testing the hypotheses, the descriptive analytical method was used to complete the research depending on the questionnaire as a main tool for collecting data, which was distributed to the research community (The Automotive and Equipment Manufacturing State Company). Senior management in the researched company included a sample of 150 respondents. Several statistical methods, including mean, standard deviation, simple regression, and Spearman correlation coefficient were used. The results showed a significant effect of strategic awareness on organizational readiness for change, and that the dimensions of strategic awareness have an efficacious and essential effect on organizational readiness. The researched company’s efforts to apply high levels of strategic awareness will reflect positively in achieving organizational readiness. Paper type: Research paper.